2019
DOI: 10.1177/2010105819860853
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial and physical factors associated with depression in older adults living in studio apartments: A cross-sectional study of a multi-ethnic Asian population

Abstract: Background: There is a rapidly ageing population globally, leading to a rise in subsidised public housing in many countries for older adults. According to the World Health Organisation, depression is the most prevalent mental disorder in older adults. There is a gap in literature on the factors associated with depression in those residing in studio apartments for older adults, characterised by small living spaces and isolated community settings. Objective: The aim of this study was to examine the associations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
1
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 50 publications
1
1
0
2
Order By: Relevance
“…The results revealed that marital status was a significant predictor for major depression among older adults, indicating that currently unmarried older adults who are predominantly those who widowed in the current study have higher levels of depression than married people. This significant association is supported by substantial literature from India as well as other countries [ 26 , 63 , 64 ]. Gahler highlights that marital dissolution is associated with severe social discord and confers an increased risk for psychological distress and overall health deterioration [ 65 ].…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The results revealed that marital status was a significant predictor for major depression among older adults, indicating that currently unmarried older adults who are predominantly those who widowed in the current study have higher levels of depression than married people. This significant association is supported by substantial literature from India as well as other countries [ 26 , 63 , 64 ]. Gahler highlights that marital dissolution is associated with severe social discord and confers an increased risk for psychological distress and overall health deterioration [ 65 ].…”
Section: Discussionsupporting
confidence: 61%
“…This study found that highly educated older adults have lower chances of depression. Previous findings also reported a negative association between educational attainment and depression [ 58 , 59 , 61 , 64 ]. Higher educational attainment can reduce the risk of depression since those who are educated may be more aware of availability and accessibility of the health services, and may have better healthcare utilization and improved health behavior among older adults [ 73 ].…”
Section: Discussionmentioning
confidence: 75%
“…Faktor status pernikahan seperti telah menjanda, kesulitan fungsi fisik, kondisi kronis, dukungan sosial yang rendah, kesehatan mental yang dianggap rendah, kepuasan hidup yang buruk dan kurangnya perilaku olahraga dikaitkan dengan gejala depresi pada orang lansia. Perhatian lebih diperlukan untuk merawat kebutuhan psikososial dan fisik lansia yang mengalami risiko depresi tersebut (Sum et al, 2019). Hasil temuan Chen et al, (2019) menggunakan metode meta-analisis kualitatif menunjukkan bahwa kehilangan, gangguan tidur, kecacatan, depresi sebelumnya dan jenis kelamin perempuan merupakan faktor risiko yang signifikan.…”
Section: Pendahuluanunclassified
“…Penelitian berkelanjutan di bidang ini diperlukan untuk memahami jalur etiologis yang mendasari asosiasi ini dan poin intervensi yang dapat dimodifikasi untuk mengurangi beban depresi akhir hidup yang tidak proporsional di antara sub kelompok populasi dengan risiko tertinggi (Mohd et al, 2019) Selanjutnya, faktor status pernikahan seperti telah menjanda, kesulitan fungsi fisik, kondisi kronis, dukungan sosial yang rendah, kesehatan mental yang dianggap rendah, kepuasan hidup yang buruk dan kurangnya perilaku olahraga dikaitkan dengan gejala depresi pada orang lansia. Perhatian lebih diperlukan untuk merawat kebutuhan psikososial dan fisik lansia yang mengalami risiko depresi tersebut (Sum et al, 2019).…”
Section: Pembahasanunclassified